2023
DOI: 10.3389/fimmu.2023.1177085
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy combined with immune checkpoint inhibitors in locally advanced/metastatic esophageal squamous cell carcinoma: clinical trials, efficacy and future directions

Abstract: Esophageal squamous cell carcinoma (ESCC) is a common malignancy worldwide and often diagnosed at advanced stages with poor prognosis. Combination of radiotherapy and immunotherapy seems to be a promising approach for treating ESCC. This comprehensive review article summarizes the current state of combination of radiotherapy and immunotherapy in locally advanced/metastatic ESCC, delineates the clinical trials that merit attention, and outlines unresolved issues and future research directions in this field. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 158 publications
(173 reference statements)
0
0
0
Order By: Relevance
“…Radiotherapy has also been shown to lead to an abscopal effect. The direct and indirect antitumor effects of radiotherapy may be further augmented by immunotherapy [17]. Immunotherapy may serve as a primer for improved response to subsequent lines of chemoradiation.…”
Section: The Relationship Between Immunotherapy and Chemoradiationmentioning
confidence: 99%
“…Radiotherapy has also been shown to lead to an abscopal effect. The direct and indirect antitumor effects of radiotherapy may be further augmented by immunotherapy [17]. Immunotherapy may serve as a primer for improved response to subsequent lines of chemoradiation.…”
Section: The Relationship Between Immunotherapy and Chemoradiationmentioning
confidence: 99%
“…The most recognized molecular markers are PD-L1, microsatellite instability and tumor mutational load, but they are still some way from being ideal predictive markers. Various external factors, including sample quality, assay conditions, and cutoff values can influence the predictive accuracy of these markers (82)(83)(84).…”
Section: Patient Selection and Predictive Markersmentioning
confidence: 99%
“…Several case reports and early clinical trials [27,59,60] have described the use of immunoradiotherapy in metastatic SCC. A recently published manuscript [59] suggested that patients with metastatic SCC who received a combination of immune checkpoint inhibitors and radiotherapy resulted in significant tumor regression and prolonged survival. Similarly, early-phase clinical trials have reported objective responses and disease control in patients with metastatic SCC receiving immunoradiotherapy [27,60].…”
Section: Metastatic Diseasementioning
confidence: 99%
“…These reports highlight the potential of immunoradiotherapy to induce tumor regression and achieve durable responses in metastatic disease. Despite the promising results [27,59,60], challenges exist in the successful implementation of immunoradiotherapy in metastatic SCC.…”
Section: Metastatic Diseasementioning
confidence: 99%